2015
DOI: 10.1007/s11164-015-2287-8
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of endo-dicyclopentadiene using a mesoporous catalyst in a fixed-bed reactor

Abstract: The oligomerization of endo-dicyclopentadiene (endo-DCPD) over a mesoporous catalyst in a continuous-flow reactor at elevated pressure was studied to produce tricyclopentadiene (TCPD) and tetracyclopentadiene (TeCPD). The mesoporous material prepared from zeolite beta (MMZ Hb ) was utilized as a catalyst. In addition, this study focused on the catalytic performance of the regenerated catalyst in comparison with the fresh catalyst. The TCPD and TeCPD were continuously produced through DCPD oligomerization over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The catalyst was heavily deactivated due to the formation of higher molecular weight hydrocarbons. After regeneration, it was found that the calcination temperature of 500 °C was effective, which maintained the activity of the catalyst with no appreciable difference from that of the fresh catalyst …”
Section: Other High Energy Density Fuelsmentioning
confidence: 98%
See 1 more Smart Citation
“…The catalyst was heavily deactivated due to the formation of higher molecular weight hydrocarbons. After regeneration, it was found that the calcination temperature of 500 °C was effective, which maintained the activity of the catalyst with no appreciable difference from that of the fresh catalyst …”
Section: Other High Energy Density Fuelsmentioning
confidence: 98%
“…After regeneration, it was found that the calcination temperature of 500 °C was effective, which maintained the activity of the catalyst with no appreciable difference from that of the fresh catalyst. 53 Zou et al 16 studied the Pd-B/γ-Al 2 O 3 catalyst as a function of various conditions in the catalyst pretreatment and its impact on the hydrogenation of TCPD into THTCPD. The reaction mechanism involves the conversion of TCPD to DHTCPD, finally hydrogenated into THTCPD at 130−150 °C with 1.5 MPa of hydrogen pressure.…”
Section: Other High Energy Density Fuelsmentioning
confidence: 99%